Women's Political Communication in Maluku: Opportunities, Challenges, and Socio-Cultural Dynamics - Afdhal Afdhal (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines women's political communication in Maluku, focusing on the opportunities, challenges, and socio-cultural dynamics they face. In a region strongly influenced by patriarchal culture, women's roles in politics are often constrained by traditional social views and resistance to their involvement in a male-dominated political arena. The complexity of this issue is heightened by the perception that politics is a harsh and competitive domain. The aim of this research is to understand the communication strategies used by female politicians in Maluku and to identify the factors that influence their success or failure in the political field. This study employs a qualitative method, gathering data through in-depth interviews with female politicians, activists, and political observers in Maluku. The findings reveal that despite significant challenges, female politicians are able to leverage local values such as community solidarity and the adat-based social system to strengthen their political positions. Additionally, social networks and support from women's groups and political organizations play crucial roles in their political communication strategies. Women's roles in Maluku politics are not limited to verbal and non-verbal communication but also include their ability to integrate local values and utilize their central societal roles to promote political agendas. These findings provide a significant contribution to the study of women's political communication, particularly in contexts that have been underexplored in both national and international literature. The research concludes that women's political communication in Maluku is a complex adaptation to the local socio-cultural context.